Are youths on income support less happy? Evidence from Australia - Wang-Sheng Lee; Umut Oguzoglu (Institute for the Study of Labor (IZA), 2007)
The central research question addressed in this paper is how receipt of income support payments affects the well-being of youths. Using 1997-2004 panel data from a nationally representative survey of Australian youths, we attempt to estimate the size of the welfare stigma faced by Australian youths, where stigma is defined as the effect of welfare receipt on reported happiness levels. In analysing the determinants of happiness, we argue that it is important to control for dynamics and initial conditions. The latter arguably measures an initial setpoint of happiness which the psychological literature has found strong support for. In contrast to the general findings of the existence of a welfare stigma for adults, based on our results using dynamic panel probit models, our findings suggest that for Australian youths, there is a small negative but not statistically significant stigma associated with welfare receipt.
urn:nbn:de:101:1-2008041089
Keywords: 330; Jugendliche; Sozialhilfeempfänger; Lebensstandard; Lebenszufriedenheit; Lebensqualität; Australien